Isolation and Time Lapse Microscopy of Highly Pure Hepatic Stellate Cells - Matthias Bartneck; Klaudia Theresa Warzecha; Carmen Gabriele Tag; Sibille Sauer-Lehnen; Felix Heymann; Christian Trautwein; Ralf Weiskirchen; Frank Tacke (Analytical Cellular Pathology)
Hepatic stellate cells (HSC) are the main effector cells for liver fibrosis. We aimed at optimizing HSC isolation by an additional step of fluorescence-activated cell sorting (FACS) via a UV laser. HSC were isolated from livers of healthy mice and animals subjected to experimental fibrosis. HSC isolation by iohexol- (Nycodenz) based density centrifugation was compared to a method with subsequent FACS-based sorting. We assessed cellular purity, viability, morphology, and functional properties like proliferation, migration, activation marker, and collagen expression. FACS-augmented isolation resulted in a significantly increased purity of stellate cells (>99%) compared to iohexol-based density centrifugation (60–95%), primarily by excluding doublets of HSC and Kupffer cells (KC). Importantly, this method is also applicable to young animals and mice with liver fibrosis. Viability, migratory properties, and HSC transdifferentiation in vitro were preserved upon FACS-based isolation, as assessed using time lapse microscopy. During maturation of HSC in culture, we did not observe HSC cell division using time lapse microscopy. Strikingly, FACS-isolated, differentiated HSC showed very limited molecular and functional responses to LPS stimulation. In conclusion, isolating HSC from mouse liver by additional FACS significantly increases cell purity by removing contaminations from other cell populations especially KC, without affecting HSC viability, migration, or differentiation.